2017
DOI: 10.1111/apa.13973
|View full text |Cite
|
Sign up to set email alerts
|

Young children with severe congenital malformations (VACTERL) expressed mixed feelings about their condition and worries about needles and anaesthesia

Abstract: Careful follow-up of these children by multidisciplinary teams is crucial to optimise their health and functional status. Fear of medical procedures may be reduced by carefully delivered information, listening to the children, providing continuity of care and creating individual care strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
5
14
0
Order By: Relevance
“…However, six children in the present study rated their well‐being between very bad and somewhat bad and 19 children rated their hospital stay as very bad to somewhat bad prior to having animal‐assisted therapy. They mentioned various negative thoughts and feelings such as pain caused by treatment or illness, fear over procedures and sadness over their illness, which is in line with findings of other researchers . For some children, the fear of the procedure might be worse than the pain itself .…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…However, six children in the present study rated their well‐being between very bad and somewhat bad and 19 children rated their hospital stay as very bad to somewhat bad prior to having animal‐assisted therapy. They mentioned various negative thoughts and feelings such as pain caused by treatment or illness, fear over procedures and sadness over their illness, which is in line with findings of other researchers . For some children, the fear of the procedure might be worse than the pain itself .…”
Section: Discussionsupporting
confidence: 80%
“…Studies have report that a hospital stay can be an overwhelming experience for children . The care has been perceived to be satisfactory, and the health professionals’ various skills have been appreciated, but the stay has also been perceived as frightening, distressful and disquieting . Findings were reported that for a family with a child diagnosed with a severe illness the patient, their parents and siblings felt that their world was falling apart .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations